The development of a real-time photogrammetric system for patient positioning in proton therapy - Van der Vlugt, Graeme (Division of Geomatics, 2026)
This thesis concerns the development of a real-time photogrammetric system for the positioning of patients undergoing proton therapy. The positioning of patients involves moving their tumours into a horizontal proton beam. In the past, patients have been mechanically positioned and restrained. However, with the development of this new "StereoPhotoGrammetric" (SPG) system, patients will be positioned using CCD cameras and digital photogrammetric techniques. A specially designed mechanical chair will move the patients at the command of the SPG system. The tumour is located relative to reference targets on a patient's head using medical imaging. In the treatment room these same targets are imaged and identified by the SPG system. The positions of these reference targets are determined in three-dimensional space and hence the relative position of the tumour can be computed. Using this knowledge, the mechanical chair is automatically sent instructions to move the patient into the desired treatment position. Once the proton beam is switched on, the SPG system monitors the patient in order to detect any movements. The beam is immediately switched off if any substantial movement takes place. As a basis, some general theory of photogrammetry is covered. The development of reliable and efficient processing routines for the SPG system and the photogrammetric procedures involved in the system, are reported in detail. The routines are composed of a combination of automatic and computer-aided manual processes. The reliability and efficiency of these various routines are evaluated. The hardware and software were successfully integrated into a functional unit, capable of positioning and monitoring patients. A number of tests of target positioning accuracy were executed with the SPG system and satisfactory results were achieved.